Evaluation of the infectivity and the persistence of Trichinella patagoniensis in muscle tissue of decomposing guinea pig (Cavia porcellus) - Farina, Fernando (2017)
Fil: Fariña, F. Universidad de Buenos Aires. Facultad de Ciencias Veterinarias. Cátedra de Parasitología y Enfermedades Parasitarias; Argentina.